Transformation Of Agriculture In Rajasthan:- An economic analyses - Maurya, Chitranjan Kumar; Tarun, Pooja (Universal Research Reports, 2017)
The article explores how Indian Agricultural libraries have evolved and transformed in the digital era and how technological advances and increased sophistication of web based tools have enabled libraries to collaborate and share resources. The authors identify various innovative practices adopted by fifty six Indian agricultural libraries and detail the collaborative county-wide programs and digitization projects in progress such as eGranth’s AgriCat, a union catalog of books and articles in agriculture and allied sciences. Also described are activities involving digital institutional repositories like KrishiKosh and KrishiPrabha and the establishment of a national level consortium for e-journals and digital content accessible to the Indian academic community. Grants from World Bank-ICAR funded projects like the National Agricultural Innovative Project (NAIP) have boosted digitization in India and have brought libraries and the user community into closer proximity virtually by removing physical boundaries.